2018
DOI: 10.1097/acm.0000000000001829
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Medical Students’ Electronic Health Record Access Can Impede Their Preparedness for Practice

Abstract: Medical students need hands-on experience documenting clinical encounters as well as entering orders to prepare for residency and become competent physicians. In the era of paper medical records, students consistently acquired experience writing notes and entering orders as part of their clinical experience. Over the past decade, however, patient records have transitioned from paper to electronic form. This change has had the unintended consequence of limiting medical students' access to patient records. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 19 publications
2
62
0
1
Order By: Relevance
“…14 Similar work also suggests that students, particularly those from IM Core residency programs, 15 may enter residency training without essential clinical documentation skills. 16 Demonstrating association between student engagement with EHRs and subsequent performance in residency is beyond the scope of this study. When data are available, future research should empirically examine the relationships between medical student levels of EHR utilization and the quality of that engagement during IM clinical experiences with their subsequent performance as IM residents.…”
Section: Discussionmentioning
confidence: 98%
“…14 Similar work also suggests that students, particularly those from IM Core residency programs, 15 may enter residency training without essential clinical documentation skills. 16 Demonstrating association between student engagement with EHRs and subsequent performance in residency is beyond the scope of this study. When data are available, future research should empirically examine the relationships between medical student levels of EHR utilization and the quality of that engagement during IM clinical experiences with their subsequent performance as IM residents.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has demonstrated wide variation in levels of EHR access among medical students, ranging from no-access to read-only access to full-access [6]. Tiwari and Kumar explored the use of algorithm-based permissions for users seeking access to patient-level EHR access by role, but their work did not seek to quantify current levels of EHR access among users across various roles [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these barriers, many usability researchers and scientists often have limited EHR access to facilitate usability testing. While EHR access status has been described among medical student [6] and remote clinician populations [7], to our knowledge there have been no prior reports of EHR access status among the broader population of informatics professionals, which importantly includes a subset of usability researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Limited opportunities for documentation reduces medical students' experiential learning and feedback. 11 If these EPAs are reasonable expectations for medical school graduation, we need to consider how undergraduate curricula can meaningfully incorporate them and develop a consistent framework for longitudinal observation. 2 We learned several lessons during implementation of this exercise.…”
Section: Figures 2a and 2b Intern Performance In Osce Stationsmentioning
confidence: 99%